The Important Role of Parents in Guiding Children in the Digital Era 4.0 - Damayanti Nababan; Elsa Yulinarda Yahya Nainggolan; Louisa Silalahi; Ayu Pasaribu; Sri Sinambela; Saryna Natalia Purba; Agnesia Mahulae; Sonia Hutauruk; Rizki Lumbantobing; Indah Gultom; Fourman Simatupang (PT PUBLIKASI INSPIRASI INDONESIA, 2023)
The role of parents in guiding children in the digital era 4.0 is becoming increasingly crucial along with advances in technology. In an ever-growing digital environment, parents play an important role as facilitators and companions for their children. This article reviews how parents can guide their children in understanding and managing the impact of technology positively. An approach that involves open communication, understanding online risks and developing digital skills together is key to ensuring that children can face digital challenges wisely. By understanding their role as mentors and actively involving themselves, parents can help shape a young generation that is able to use technology responsibly in this dynamic digital era. In the digital era 4.0, the challenges faced by children in facing technological advances require a proactive and caring role from parents. This research discusses the central role of parents as supervisors and educators in guiding their children to face the complex digital world. Open communication and a deep understanding of technology are key to creating a safe and educational environment. Parents need to develop digital literacy with their children, facilitate understanding of online etiquette, and provide adequate guidance regarding the use of digital devices. In addition, this article highlights the need for parents as positive role models, helping children build critical and emotional skills to face the challenges of the digital era. Thus, the role of parents is not only limited to supervision, but also to active guidance to create a generation that is intelligent, responsible and digitally skilled.